2015
DOI: 10.1039/c4ra11137k
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide release by N-(2-chloroethyl)-N-nitrosoureas: a rarely discussed mechanistic path towards their anticancer activity

Abstract: Our work shows that NO release is a feasible pathway of action for aromatic and heterocyclic N-(2-chloroethyl)-N-nitrosoureas and faster NO release may not lead to higher cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…MCF-7 was one of the used lines in Collins et al (2012) study in which they suggest that trastuzumab can bind cells of low HER-2 level or negative and initiate antibody-dependent cell-mediated cytotoxicity [30]. Another study showed an additive interaction between trastuzumab and docetaxel or paclitaxel in HER2-weak to moderate or higher expressing cells, that may suggest that trastuzumab has a role in inhibiting her2 negative tumors by other unknown mechanism [31].…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 was one of the used lines in Collins et al (2012) study in which they suggest that trastuzumab can bind cells of low HER-2 level or negative and initiate antibody-dependent cell-mediated cytotoxicity [30]. Another study showed an additive interaction between trastuzumab and docetaxel or paclitaxel in HER2-weak to moderate or higher expressing cells, that may suggest that trastuzumab has a role in inhibiting her2 negative tumors by other unknown mechanism [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this particular moiety exhibited significant antimicrobial activity against A. nidulans fungi . Similarly, N -nitrosoureas, a particular class of N -nitrosamines, were used as anticancer agents because of their DNA alkylation activities. , Though N -nitrosamines are not as familiar as NONOates and RSNOs, they are useful for developing photoinduced NO donors.…”
Section: No-releasing Motifs and Lmw No Donorsmentioning
confidence: 99%
“…Carmustine (1,3-bis(2-chloroethyl)-1-nitrosourea, C 5 H 9 Cl 2 N 3 O 2 , Figure 1, internally called “Carinamustine” due to the name of the first author) is an antineoplastic nitrosourea used in the treatment of several forms of malignant tumors, especially against leukemia and brain tumors (Weiss and Ijssel, 1982; Sarkar et al , 2015; Wang et al , 2017). Carmustine belongs to the nitrosoureas which have the cytotoxic effect of alkylating of the DNA and therefore can decelerate the growth of cancer cells by inhibiting the vital processes such as replication, transcription, and translation of DNA (Hadidi et al , 2019).…”
Section: Introductionmentioning
confidence: 99%